2015
DOI: 10.2112/si73-007.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Dynamic Wave Force on Seabed around a Geotextile Mattress with Floating Curtain

Abstract: Xie, L.; Zhu, Y.; Huang, W., and Liu, C., 2015. Experimental investigations of dynamic wave force on seabed around a geotextile mattress with floating curtain.A new technique called geotextile mattress with floating curtain (GMFC) may be an advisable alternative countermeasure against seabed erosion, since it can allow deposited sediment dunes to form naturally at upstream and downstream sides of GMFC when installed in erosive flow. However, cyclic loading of wave actions can lead to liquefaction of the seabed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…If properly designed, the local scour near the flexible structures is less significant compared with that of rigid structures. Such structures include inflatable flexible membrane dams [22], mattress curtain sets [23], fiber reinforced mats [24], suspended curtains [25], geotextile mattress with sloping curtain [26,27], geotextile mattress with sloping plate [28], etc.…”
Section: Introductionmentioning
confidence: 99%
“…If properly designed, the local scour near the flexible structures is less significant compared with that of rigid structures. Such structures include inflatable flexible membrane dams [22], mattress curtain sets [23], fiber reinforced mats [24], suspended curtains [25], geotextile mattress with sloping curtain [26,27], geotextile mattress with sloping plate [28], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [28] studied the response of bed pressure distribution adjacent to a GMSC in wave conditions with a hydraulic flume. The result indicated that the largest cyclic force appears at about a distance of the curtain height to the centerline of the GMSC.…”
Section: Introductionmentioning
confidence: 99%